Biofuels and Sustainability Holistic Perspectives for Policy-making - Takeuchi, Kazuhiko; Shiroyama, Hideaki; Saito, Osamu; Matsuura, Masahiro; SpringerLink (Online service) (Tokyo : Springer Japan : Imprint: Springer, 2018)
This open access book presents a comprehensive analysis of biofuel use strategies from an interdisciplinary perspective using sustainability science. This interdisciplinary perspective (social science-natural science) means that the strategies and policy options proposed will have significant impacts on the economy and society alike. Biofuels are expected to contribute to reducing greenhouse gas emissions, revitalizing economies in agricultural communities and alleviating poverty. However, despite these anticipated benefits, international organizations such as the FAO, OECD and UN have published reports expressing concerns that biofuel promotion may lead to deforestation, water pollution and water shortages. The impacts of biofuel use are extensive, cross-sectoral and complex, and as such, comprehensive analyses are required in order to assess the extent to which biofuels can contribute to sustainable societies. Applying interdisciplinary sustainability scienceconcepts and methodologies, the book helps to enhance the establishment of a sustainable society as well as the development of appropriate responses to a global need for urgent action on current issues related to biofuels.
Preface.-Introduction.-Part 1: Biofuels and Sustainability Conceptual Framework -- Chapter 1. Sustainability Science Perspective for Biofuels [Takeuchi, Matsuda] -- Chapter 2. Stakeholder perspectives and Multilevel Governance [Shiroyama, Matsuura] -- Chapter 3. Applying stakeholder perspectives to sustainable biofuel strategy: a summary of our analyses [Shiroyama, Matsuura].-Part 2: Impacts on land use and ecosystem services -- Chapter 4. Global Economic and Environmental Impacts - Economic Impacts of biofuels and related policy [Suzuki and Takahashi] -- Chapter 5. Global Economic and Environmental Impacts - Environmental impacts of biofuel production on the GHG emission reduction [Hanaki] -- Chapter 6. Impacts at the National & Regional Scales - Land use change impacts [Hayashi] -- Chapter 7. Impacts at the National & Regional Scales - Socioeconomic impacts in East Asia [Elder, Kozima, Sano and Hayashi] -- Chapter 8. Social, Economic and Political Impacts - Socio-Political impactsto the roles of stakeholders [Shiroyama and Matsuura ] -- Chapter 9. Social, Economic and Political Impacts - Impacts on ecosystem services [Alexandros and Stromberg] -- Part 3: Sustainable biofuels strategy options -- Chapter 10. Roadmap for building sustainable strategy options - Developing sustainable strategy options [Shiroyama and Matsuura] -- Chapter 11. Roadmap for building sustainable strategy options - Application of Ontology for developing strategy options [Kozaki, Mizoguchi and Saito] -- Chapter 12. Key strategies for policy makers - Global Strategies options [Arai, Matsuda and Suzuki] -- Chapter 13. Key strategies for policy makers - Regional Strategy options for East Asia [Elder, Kozima, Sano and Hayashi] -- Chapter 14. Key strategies for policy makers - National strategy options for Japan [Shiroyama, Matsuura and Saito].
Keywords: Sustainability; Energy policy; Energy and state; Biotic communities; Environmental management; Renewable energy sources; Environmental Law; Sustainability; Energy Policy, Economics and Management; Ecosystems; Environmental Management; Renewable Energy; Environmental Law